Effects of Combining Compost, Nitrogen, and Phosphorus on Barley Production in Wag-Lasta, Ethiopia. - Ashebir, Merse Mengesha; Dejene, Dereje; Gashaw, Tadese (Food, Agriculture and Natural Resources - NETWORKS, 2025)
This trial aimed to assess the composting potential of local materials and their integration with inorganic fertilizers to enhance barley productivity. The experiment involved preparing compost and evaluating its effects on barley production at two locations over two years. Mean treatment differences were analyzed using the analysis of variance (Proc-GLM) procedure. The combined analysis over the two years in the Dahana and Lalibela areas revealed that applying the recommended blanket inorganic fertilizer resulted in the highest biomass and grain yield. However, using one tone of compost along with half of the recommended nitrogen and phosphorus also achieved comparable biomass and grain yield. Additionally, this approach improved the soil's physical and chemical properties over time. Therefore, using one ton of compost with half the recommended nitrogen and phosphorus is recommended for the Wag and Lasta highlands and similar agro-ecologies where barley is grown.